AI-Driven Marketing Solutions For Ethical Product Branding In MSMES - Erwin Ernestus Kadar Slamet; Tiur Ayya Zakiyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to explore the efficacy of AI-driven marketing solutions in facilitating ethical product branding within Micro, Small, and Medium Enterprises (MSMEs). The research adopts a descriptive model, employing purposive sampling to gather data from a diverse range of MSMEs engaged in ethical product branding practices. Data analysis utilizes thematic analysis to identify patterns and insights from qualitative data. The study aims to unveil the impact of AI-driven marketing strategies on enhancing sustainability and ethical branding efforts among MSMEs. Results are expected to shed light on the effectiveness of these solutions in fostering responsible consumerism and promoting sustainable business practices within the MSME sector, thereby contributing to the discourse on ethical marketing and sustainable development.